Development of Digital Storytelling Based on Local Wisdom for Strengthening the Pancasila Student Profile in High Schools throughout Kediri Regency - Ganes Tegar Derana; Angellia Ratna Putri Yurita (Universitas Mulawarman, 2026)
This research is motivated by the urgency of moral value degradation among Generation Z amidst the massive wave of digitalization, as well as the need for learning media innovations that are aligned to strengthen the achievement of the Pancasila Student Profile (P5) in Senior High Schools (SMA). This study aims to develop, test the feasibility, and evaluate the effectiveness of Digital Storytelling (DST) media based on local wisdom, specifically the Panji Kediri Story Cycle. The approach used is Research and Development (R&D) with the ADDIE model framework (Analysis, Design, Development, Implementation, Evaluation). Data collection was conducted comprehensively through expert validation sheets, practicality response questionnaires, as well as observation and self-assessment rubrics to measure the dimensions of Critical Thinking and Global Diversity. The validation results showed a feasibility level predicated as